Disinformation in Spain one year after COVID-19. Analysis of the Newtral and Maldita verifications. - Almansa-Martínez, Ana María; Fernández-Torres, María Jesús; Rodríguez-Fernández, Leticia (Historia de los Sistemas Informativos, 2022)
Introduction. One year after the beginning of the state of alarm in Spain, a study has been carried out to check the situation of fake news. Methodology. A content analysis of all the checks made by the fact checking platforms Maldito Bulo and Newtral during the month of the anniversary (March 14 to April 14, 2021) has been carried out. In total, 255 fact checks were analyzed. Results. The fake news that are spreading the most are related to the political debate, beyond the pandemic. The most disseminated content related to the health crisis are linked to vaccines and the vaccination process. Almost a quarter of the hoaxes have the Spanish Government, regional governments and other institutions as protagonists, with the Spanish Executive being the most commented. On the other hand, half of the false information detected has been created by people who are not socially known or whose identity is unknown, as well as by the media and opposition parties. Conclusions and Discussion. We found that fake news about COVID-19 account one year later for a little more than a quarter of all existing hoaxes, which is a clear decrease compared to the first months of the pandemic. Fake news continues to be spread especially by Twitter and WhatsApp
Desinformación en España un año después de la COVID-19. Análisis de las verificaciones de Newtral y Maldita
Keywords: Medios de comunicación social - Objetividad; COVID-19; Spain; Fake news; Disinformation; Verification; Infodemic